A leitura da documentação pedagógica com o crivo de referenciais freireanos: subsídios para uma formação de professoras que trabalham com bebês e crianças pequenas - Cardoso, Rosimeire dos Santos (2018)
This research aims to investigate how pedagogical documentation can be a valuable tool to subsidize the continuing education of early childhood teachers in a critical-reflective perspective. The theoretical reference concerning the formation of teachers is based on principles of Paulo Freire’s Pedagogy (2001, 2016, 2017). Regarding pedagogical documentation, the research is based on the conception and practice by teacher Reggio Emilia, expressed by Edwards, Gandini and Forman (1999, 2016). The analysis methodology has a qualitative approach and the instruments that helped to understand the context studied were: the analysis of the documents produced by the teachers of a Municipal Education Schools in São Paulo city and the semi structured interview, applied to the teachers, with the purpose to know the understanding and value attributed to the production of pedagogical records. The data produced were analyzed upon Paulo Freire's concepts theoretical framework, expressed in a conceptual structure that presents as the center of the discussions the practice and the teacher formation from the following concepts: critical reflection on the practice, reality’s reading, experience knowledge, dialogue and transformation of reality. The findings of this study allowed me to reflect on the improvement of my work as pedagogical coordinator of the CEI Jardim Miliunas, in order to integrate valuable results of this research into the ongoing formation of teachers, based on Freirean principles, in a critical-reflective perspective. This research may offer contributions to the understanding of registration as an important contribution to the critical reflection in early childhood teachers about their practice, especially in the process of continuing education, in the context of the school, a space in which one can collectively discuss the reasons for the choices based on experiences with children, creating conditions for the transformation of teaching practice